The Himyarite State and its Political relations with the Kingdoms of Central and northern Arabia (between the fourth and sixth centuries AD) - Koleib, Dr. Mahyoub Ghaleb Ahmed (Journal of the Faculty of Education, 2023)
The research aims to study the political relations of the Himyarite state with the kingdoms of central and northern Arabia (between the fourth and sixth centuries AD). The research attempts to give an integrated analysis of all aspects of the relations and their results to make the historical scene very clear. The research also attempts to analyze the issue of the emergence and development of those kingdoms, and their role not only in the history of the Arabian Peninsula in the first half of the first millennium AD, but also their role in the history of international relations of the ancient Near East at that time. The research has concluded that southern Arabia witnessed severe and stormy tensions and conflicts on the political, military, social and cultural levels during the first three centuries after the birth of Christ. The features appeared during the fourth and fifth centuries AD. A section of the Kinda tribes migrated - during the unrest - to the interior regions of the Arabian Peninsula. The second half of the fourth century AD witnessed the birth of a central state over all southern Arabia. The conflict that took place in southern Arabia during the sixth century AD had an impact on the deterioration of the economic, political and social conditions of the state and society alike.